Search for quark contact interactions in dijet angular distributions in pp collisions at √s = 7 TeV measured with the ATLAS detector - Anduaga, Xabier Sebastián (2016)
Dijet angular distributions from the first LHC pp collisions at center-of-mass energy √s = 7 TeV have been measured with the ATLAS detector. The dataset used for this analysis represents an integrated luminosity of 3.1 pb−1. Dijet χ distributions and centrality ratios have been measured up to dijet masses of 2.8 TeV, and found to be in good agreement with Standard Model predictions. Analysis of the χ distributions excludes quark contact interactions with a compositeness scale Λ below 3.4 TeV, at 95% confidence level, significantly exceeding previous limits.